An Empirical Study Evaluating the Symbiotic Efficiency of China’s Provinces and the Innovation Ecosystem in the High-Tech Industry - Jianzhao Yang (Complexity)
The traditional innovation model has been unable to adapt to high-speed development, so the role of the innovation ecosystem has become more important. In this paper, we introduce ecology into industrial innovation and construct the symbiotic model to study the symbiotic evolution process of the high-tech industrial innovation ecosystem. This paper takes China’s national high-tech industrial park as a case to study its symbiotic efficiency through empirical research, which uses a stochastic frontier analysis as a research method, constructs a complete index evaluation system, and analyzes the influencing factors. According to the results, we find that an environment conducive to the symbiotic efficiency has emerged, but development and efficiency of high-tech ecosystems in different regions of China are highly dispersed and unbalanced. There is room for improvement in symbiosis efficiency, but the difficulty is gradually increasing. Based on the evaluation of symbiotic efficiency of innovation ecosystem of high-tech industry and the consideration of influencing factors such as policy, economy, society, and technology, this paper puts forward the countermeasures of high-tech industry supporting regional economy.